PEMBERIAN EDUKASI GIZI MENGUNAKAN BUKU SAKU BERBASIS MEDIA ONLINE KEPADA IBU HAMIL DI KOTA PADANG PANJANG - Helmizar Helmizar; Hafifatul Aulia Rahmi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
The low nutritional status of the social community facing Indonesia is a social problem in society that will have an impact on the quality of human resources, because it will affect intelligence, immunity to disease, infant mortality, maternal mortality, and work productivity. Stunting is a chronic malnutrition problem caused by a lack of nutritional intake for a long time, resulting in growth problems in children, namely the child's height is lower or shorter (stunted) than the standard age. Based on data from Basic Health Research in 2010, it is known that the prevalence of stunting under five has reached 35.6% and has increased in 2013, namely 37.2%. The prevalence of stunting was higher than the prevalence rate of malnutrition and malnutrition (17.9%), underweight children (13.3%), and obese children (14%). The aim of this community service is to provide education to 30 pregnant women through online media. With this service activity, it is hoped that it can reduce the number of stunting and mortality in children starting from the area of the City of Padang Panjang. Activities are carried out through the media whatsapps for 4 four meetings. The data collected were data on changes in maternal weight before and after the intervention. While the data analysis used paired sample t t-test. Statistical results show that there is a difference in average body weight before and after education with a p p-value of 0.003. Nutrition education can increase body weight and nutritional problems in pregnant women so that they can give birth to healthy and smart children.